1992
DOI: 10.2307/1964346
|View full text |Cite
|
Sign up to set email alerts
|

Representative Democracy and State Building in the Progressive Era

Abstract: I draw upon state-building and legislative literatures to investigate how constituency-based representative institutions in the Progressive Era nationalized innovative public policies, thereby expanding the authority of the federal government as a component of the modern American state developing at that time. Using state-level referenda votes as measures of grassroots views, multivariate analysis discloses the impact of district opinion, as well as party and district economy, as major determinants of House ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Although much of the groundwork for the building of the new American state at the national level was laid during the Progressive Era (Carpenter 2001; Kolko 1963; Link and McCormick 1983; McDonagh 1992; Sklar 1998; Skocpol 1992; Skowronek 1982; Wiebe 1967), with few exceptions (Hays 1964; Huthmarcher 1962), little scholarly attention has focused on the seemingly contradictory devolution of institutional power to citizens at the subnational level that resulted from the adoption of direct democracy reforms. Most notably, scholars have yet to adequately explain why nearly half the state legislatures decided to divest themselves of their monopoly control over lawmaking during this era, a development that appears to run against the expansive tide of institutionalization that centralized and consolidated governing authorities.…”
Section: Adopting Direct Democracy: Temporality and Case Selection Comentioning
confidence: 99%
“…Although much of the groundwork for the building of the new American state at the national level was laid during the Progressive Era (Carpenter 2001; Kolko 1963; Link and McCormick 1983; McDonagh 1992; Sklar 1998; Skocpol 1992; Skowronek 1982; Wiebe 1967), with few exceptions (Hays 1964; Huthmarcher 1962), little scholarly attention has focused on the seemingly contradictory devolution of institutional power to citizens at the subnational level that resulted from the adoption of direct democracy reforms. Most notably, scholars have yet to adequately explain why nearly half the state legislatures decided to divest themselves of their monopoly control over lawmaking during this era, a development that appears to run against the expansive tide of institutionalization that centralized and consolidated governing authorities.…”
Section: Adopting Direct Democracy: Temporality and Case Selection Comentioning
confidence: 99%
“…Thus in order to understand the historical background of the UCR system, it is essential to look at the profound changes in the governmental system in the US in the late nineteenth and early twentieth centuries. Scholars have shown that there was a significant expansion and centralization of power of the federal government in the late‐eighteenth and early‐nineteenth centuries in American history [McDonagh 1992, Orloff 1988, Skocpol 1992, Skowronek 1982]. The extension of the authority and resources of the federal government was also accompanied by the development of a more rationalized managerial outlook to public administration tied to the Progressive era credo of scientific governance.…”
Section: Resultsmentioning
confidence: 99%
“…For an analysis of the effects of policy congruence upon state-building processes see McDonagh (1992). For an analysis of the effects of policy congruence upon state-building processes see McDonagh (1992).…”
Section: Resultsmentioning
confidence: 99%